(untitled) (The Research of Medical Science Review, 2025)
Pseudomonas aeruginosa is a multidrug-resistant pathogen that poses a serious threat to immunocompromised individuals, necessitating novel vaccine strategies. This study employed an integrative immunoinformatics and structural bioinformatics approach to design a multi-epitope peptide vaccine targeting the conserved Flagellin A protein of P. aeruginosa. B-cell, cytotoxic T lymphocyte (CTL), and helper T lymphocyte (HTL) epitopes were identified and screened based on antigenicity, non-allergenicity, and human non-homology. The selected epitopes were assembled into eight vaccine constructs using appropriate linkers and adjuvants, and modeled using AlphaFold v3. Among them, construct 7 emerged as the most promising candidate, exhibiting superior structural stability (ERRAT score: 98.27; >90% residues in favored Ramachandran regions) and optimal physicochemical properties, including a low instability index and high solubility. Molecular docking demonstrated strong binding affinities of the epitopes with MHC class I (HLA-A11:01), MHC class II (HLA-DQB1*03:01), and innate immune receptors TLR4 and TLR5, with binding energies as low as −189.76 kcal/mol. Immune simulations predicted strong IgG and IgM responses, T-cell activation, and cytokine release, indicating a balanced humoral and cellular immune response. Codon optimization (CAI: 1.0; GC content: 53.03%) and in silico cloning into the pET28a (+) vector confirmed high expression potential in E. coli K12, supported by favorable mRNA structure and ribosomal docking. Overall, construct 7 represents a stable, immunogenic, and expressible vaccine candidate, offering a promising avenue for future experimental validation against P. aeruginosa infections.